The Implementation of Critical Thinking in a Saudi EFL Context: Challenges and Opportunities - Budor Saeed Al Zahrani; Tariq Elyas (Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2017)
The aim of this paper is to explore the challenges to, and benefits of, fostering of critical thinking (CT) in the Saudi EFL (English as a foreign language) context. In the next section, the concept of CT will be clarified. In the following two sections, possible challenges or barriers to CT, whether religious or pedagogical, in the Saudi context are analyzed and refuted. After discussing the religious and the educational background of this issue, practices for promoting CT inside EFL classrooms are described. Finally, the benefits of incorporating CT strategies into language learning are outlined.